Recovery air kondensat pada stasiun perebusan untuk menekan oil losses: studi kasus PKS Cot Girek - Eti Indarti; Dicky Aulia Zulmi; Zaidiyah Zaidiyah; Zulhadi Zulhadi (AGROINTEK, 2022)
This study aims to reuse condensate water from sterilization stations to reduce oil losses; a case study at PKS Unit of PT. Perkebunan Nusantara I Cot Girek, North Aceh. Oil losses, a common problem in most crude palm oil (CPO) production, in the PKS Unit reach 0.71%, exceeding the company's standard of 0.6%. Among the possible oil losses, the sterilization station is concerned in this study due to the high content oil (0.86%) of the condensate water discharged from the station still. Therefore, the addition of a reservoir for condensate water is required to settle the impurities, and then this treated water is reused as diluent water in the oil gutter station. As a result, the overall oil losses in the fat pit reduce from 0.71% to 0.67%. Although the reduction of oil losses is only 0.04%, the cost-benefit of the reservoir addition is worthy 51.2 million rupiahs per month.